The Impact Project Based Learning of Animation-Assisted Videos on the Capability for Creative Thinking in Light of Self Efficacy - Kartikasari Kartika; Yurniwati Yurniwati; Karsih (Elementary Teacher Education Program, Majalengka University, 2024)
Preparing pupils for the difficulties of the twenty-first century is the goal of basic education. One of the skills of the twenty-first century is the capacity for the creative thought. Students who study mathematics are able to develop creative thingking skills and behaviors that are valuable in life. However, in fact, based on preliminary studies, students' creative thinking ability in elementary school is still low. This is because learning is still centred on memory and finding the right answers to the questions given. The aim of this research is to ascertain how Project Based Learning, with the support of animated movies, affects students capacity for creative thought in relation to students self-efficacy. This study used cluster random sampling, quasi-eksperimental methodology (pretest posttest), and quantitative analysis. The study’s findings indicate that students who participate in Project Based Learning with video animation have higher creative thinking skills than those who enrol in expository learning, there was an interaction between the learning model and self-efficacy on creative thinking skills students with high self-efficacy were more able to think creatively in Project Based Learning with animated videos than in expository learning, and students with low self-efficacy in expository learning were more able to think creatively in Project Based Learning with animated videos. Keywords: Project Based Learning; Creative Thinking Ability; Self Efficacy Tujuan pendidikan dasar yaitu mempersiapkan peserta didik siap menghadapi tantangan abad 21. Kemampuan berpikir kreatif adalah salah satu keterampilan abad ke-21. Pembelajaran matematika memungkinkan siswa untuk dapat berpikir kreatif sehingga memiliki keterampilan dan perilaku yang penting dalam kehidupan. Namun, pada kenyataannya, berdasarkan studi pendahuluan, kemampuan berpikir kreatif siswa di sekolah dasar masih rendah. Hal ini dikarenakan pembelajaran masih berpusat pada daya ingat dan menemukan jawaban yang tepat atas pertanyaan yang diberikan. Tujuan dari penelitian ini untuk mengetahui bagaimana pembelajaran Project Based Learning berbantuan video animasi mempengaruhi kemampuan berpikir kreatif peserta didik dalam kaitannya dengan self efficacy peserta didik. Penelitian ini menggunakan teknik cluster random sampling, metodologi quasi eksperimen (pretest posttest), dan analisis kuantitaif. Hasil penelitian menunjukkan bahwa peserta didik yang mendapat pembelajaran Project Based Leraning berbantuan video aniamsi memiliki kemampuan berpikir kreatif lebih tinggi dibandingkan dengan peserta didik yang mendapat pembelajaran ekspositori, terdapat interaksi antara model pembelajaran dan self efficacy terhadap keterampilan berpikir kreatif, peserta didik dengan self-efficacy tinggi lebih mampu berpikir kreatif pada pembelajaran Project Based Learning berbantuan video animasi dibandingkan pada pembelajaran ekspositori, siswa dengan self efficacy rendah pada pembelajaran ekspositori lebih mampu berpikir kreatif dibandingkan pada pembelajaran Project Based Learning berbantuan video animasi. Kata Kunci: Project Based Learning; Kemampuan Berpikir Kreatif; Self Efficacy